Pengaruh Literasi Keuangan dan Digital Payment terhadap Perilaku Konsumtif Generasi Z di Kelurahan Paccinongang Kabupaten Gowa - Nur Annisa Sudirman; M. Ikhwan Maulana Haeruddin; Anwar Anwar; Nurman Nurman; Annisa Paramaswary Aslam (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of financial literacy and digital payment on the consumptive behavior of Generation Z in Paccinongang Village, Gowa Regency. The research method used is a quantitative approach with a causal design. Data were collected through questionnaires distributed to 110 respondents of Generation Z residing in Paccinongang Village who had used digital payment, using purposive sampling. Data analysis was performed using multiple linear regression with SPSS. The results show that financial literacy has a positive and significant effect on consumptive behavior, with a regression coefficient of 0.401, t-count of 9.705, and significance of 0.000. Digital payment also has a positive and significant effect on consumptive behavior, with a regression coefficient of 0.447, t-count of 11.429, and significance of 0.000. Simultaneously, financial literacy and digital payment have a significant effect on consumptive behavior with an F-count of 124.540 and significance of 0.000. The Adjusted R-square value of 69.4% indicates that both independent variables are able to explain the variation in consumptive behavior at a high category. This means that the higher the level of financial literacy and the intensity of digital payment usage, the higher the consumptive behavior of Generation Z in Paccinongang Village, Gowa Regency.